Nuclear issue instead of Iran policy? Europe's difficult position between Iran and the US - Johannes Reissner (Stiftung Wissenschaft und Politik (SWP), 2005)
In March 2005 the third round of negotiations between Europe and Iran on Iran's nuclear program took place. It is questionable whether the United States are prepared to support Europe's attempts to use political, economic, and technological incentives to make Iran fundamentally renounce its uranium enrichment program. It is also uncertain how long Iran will be able to keep up the temporary suspension of uranium enrichment on the domestic front. Mutual mistrust and Iran's poor image in Europe impair the atmosphere of the negotiations. Moreover, Europe's Iran policy is at risk of being reduced to the nuclear issue. The Europeans could thus run into the dilemma of having to choose between Iran and the US, which would restrict their political options vis-à-vis Iran and the region and also be detrimental to their long-term interests. (SWP comments /SWP)
Keywords: 320